Synthesis and Evaluation of Two Long-Acting SSTR2 Antagonists for Radionuclide Therapy of Neuroendocrine Tumors - Sofia Koustoulidou; Maryana Handula; Corrina de Ridder; Debra Stuurman; Savanne Beekman; Marion de Jong; Julie Nonnekens; Yann Seimbille (MDPI AG, 2022)
Somatostatin receptor subtype 2 (SSTR2) has become an essential target for radionuclide therapy of neuroendocrine tumors (NETs). JR11 was introduced as a promising antagonist peptide to target SSTR2. However, due to its rapid blood clearance, a better pharmacokinetic profile is necessary for more effective treatment. Therefore, two JR11 analogs (8a and 8b), each carrying an albumin binding domain, were designed to prolong the blood residence time of JR11. Both compounds were labeled with lutetium-177 and evaluated via in vitro assays, followed by in vivo SPECT/CT imaging and ex vivo biodistribution studies. [177Lu]Lu-8a and [177Lu]Lu-8b were obtained with high radiochemical purity (>97%) and demonstrated excellent stability in PBS and mouse serum (>95%). [177Lu]Lu-8a showed better affinity towards human albumin compared to [177Lu]Lu-8b. Further, 8a and 8b exhibited binding affinities 30- and 48-fold lower, respectively, than that of the parent peptide JR11, along with high cell uptake and low internalization rate. SPECT/CT imaging verified high tumor accumulation for [177Lu]Lu-8a and [177Lu]Lu-JR11 at 4, 24, 48, and 72 h post-injection, but no tumor uptake was observed for [177Lu]Lu-8b. Ex vivo biodistribution studies revealed high and increasing tumor uptake for [177Lu]Lu-8a. However, its extended blood circulation led to an unfavorable biodistribution profile for radionuclide therapy.